The Effect of Leadership Style and Compensation on Employee Performance at the Aviary Bintaro Hotel - Munarsih, Munarsih; Harsono, Yhonanda; Arianto, Nurmin (Journal Socio Humanities Review, 2023)
The purpose of this study was to determine the effect of leadership style and compensation on employee performance at the Aviary Bintaro Hotel. The method used in this research is descriptive with an associative approach. The sampling technique used is census or saturated sampling with a sample of 85 respondents. The analysis tool uses instrument testing, classical assumption testing, regression testing, correlation coefficient testing and the coefficient of determination as well as hypothesis testing. Based on the results of the study, it shows: (1) Leadership style has a positive and significant effect on employee performance with t count > t table or (6.327 > 1.989). (2) Compensation has a positive and significant effect on employee performance with t count > t table or (6.398 > 1.989). (3) Leadership style and compensation have a positive and significant effect on employee performance with a value of Fcount>Ftable or (27.259 > 2.720).